2008
DOI: 10.1063/1.2990754
|View full text |Cite
|
Sign up to set email alerts
|

High efficient photovoltaics in nanoscaled ferroelectric thin films

Abstract: Photovoltaic effect in ferroelectric thin films with thickness below 100nm was investigated through both theoretical and experimental approaches. Unprecedented high photovoltaic power conversion efficiency around ∼0.28% was achieved with epitaxial (Pb0.97La0.03)(Zr0.52Ti0.48)O3 ferroelectric thin films, which is about 2 orders of magnitude higher than the reported in literature for ferroelectrics. Theoretical analysis indicated that efficiency can be further significantly improved by reducing the thickness in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
175
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(184 citation statements)
references
References 30 publications
2
175
1
6
Order By: Relevance
“…Although ferroelectric photovoltaics are currently receiving a great deal of interest, the origins of their photovoltaic properties are considered unresolved. Attention has been focused on interface effects, crystal orientation, and the influence of grain boundaries and defects, while any bulk photovoltaic contributions have been largely ignored [9][10][11][12][13][14][15][16][17][18]. Its mechanism has been proposed to be a combination of nonlinear optical processes, especially the phenomenon termed the ''shift current'' [19][20][21][22], but this has not been firmly established, and the detailed dependence on material properties, especially in ferroelectrics, is not known.…”
Section: First Principles Calculation Of the Shift Current Photovoltamentioning
confidence: 99%
“…Although ferroelectric photovoltaics are currently receiving a great deal of interest, the origins of their photovoltaic properties are considered unresolved. Attention has been focused on interface effects, crystal orientation, and the influence of grain boundaries and defects, while any bulk photovoltaic contributions have been largely ignored [9][10][11][12][13][14][15][16][17][18]. Its mechanism has been proposed to be a combination of nonlinear optical processes, especially the phenomenon termed the ''shift current'' [19][20][21][22], but this has not been firmly established, and the detailed dependence on material properties, especially in ferroelectrics, is not known.…”
Section: First Principles Calculation Of the Shift Current Photovoltamentioning
confidence: 99%
“…[1][2][3][24][25][26] Both experimental and theoretical works have shown that the FPV effect is different from that in conventional p-n junctions or Schottky barriers of the semiconductors. [18][19][20][21][22][23][24][25][26][27] Although a complete understanding of the physical mechanisms involved in the FPV effect in metal-ferroelectric-metal ͑MFM͒ structures with the shortcircuit boundary conditions has not yet been accomplished, a widely accepted explanation of the photoelectric current is the separation of the photon-generated electron-hole pairs ͑excitons͒ by the internal electric field, [20][21][22][23][24] which also provides the potential difference that drives the photocurrent in the external circuit connected to the ferroelectrics. In absence of an external electric field, the internal electric field comes from the depolarization field produced by polarization screening charges in the metal electrodes and the inhomogeneous polarization distribution near interfaces.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…Recent experimental and theoretical works have established that among all known perovskite ferroelectric materials, ͑Pb 0.97 La 0.03 ͒ ϫ͑Zr 0.5 Ti 0.5 O 3 ͒ ͑PLZT͒, or BFO could be the most promising candidates for photoelectric applications. [16][17][18][19][20][21][22][23][24] Photovoltaic effects occur generally in systems with asymmetric interfaces, such as semiconducting p-n junctions or metal-semiconductor interfaces with Schottky barriers. [1][2][3][24][25][26] Both experimental and theoretical works have shown that the FPV effect is different from that in conventional p-n junctions or Schottky barriers of the semiconductors.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…[8][9][10][11] Recently the highest power-conversion efficiencies ͑0.28% for narrow-band ultraviolet light, which corresponds to ϳ0.005% efficiency under sunlight͒ for ferroelectric thin films were reported in a La-doped PZT-based device. 11 The efficiency of such systems, however, remains small as a direct consequence of the relatively large band gaps of these materials although there have been proposed structures to address such limitations. 12 The emergence of lower band gap ferroelectrics oxides such as BiFeO 3 ͑BFO͒, offers an exciting opportunity to explore new materials.…”
mentioning
confidence: 99%